2011
DOI: 10.1289/ehp.1003123
|View full text |Cite
|
Sign up to set email alerts
|

Isothiocyanates Reduce Mercury Accumulation via an Nrf2-Dependent Mechanism during Exposure of Mice to Methylmercury

Abstract: Background: Methylmercury (MeHg) exhibits neurotoxicity through accumulation in the brain. The transcription factor Nrf2 (nuclear factor erythroid 2-related factor 2) plays an important role in reducing the cellular accumulation of MeHg.Objectives: We investigated the protective effect of isothiocyanates, which are known to activate Nrf2, on the accumulation of mercury after exposure to MeHg in vitro and in vivo.Methods: We used primary mouse hepatocytes in in vitro experiments and mice as an in vivo model. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
66
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 95 publications
(74 citation statements)
references
References 45 publications
7
66
1
Order By: Relevance
“…Under oxidative stress, the excessive ROS induces an increase in GST levels, and then GST metabolizes the toxic products of lipid peroxidation, and other molecules [50]. In our study, a significant decrease in the GST activity was observed after arsenic treatment, which usually occurs under extreme oxidative stress conditions [6].…”
Section: Resultssupporting
confidence: 50%
“…Under oxidative stress, the excessive ROS induces an increase in GST levels, and then GST metabolizes the toxic products of lipid peroxidation, and other molecules [50]. In our study, a significant decrease in the GST activity was observed after arsenic treatment, which usually occurs under extreme oxidative stress conditions [6].…”
Section: Resultssupporting
confidence: 50%
“…We previously reported that MeHg activates NF-E2-related factor 2 (Nrf2), a transcription factor involved in cellular protection against MeHg toxicity in human neuroblastoma SH-SY5Y cells (Toyama et al, 2007(Toyama et al, , 2011. Although such a transcription factor is known to cooperatively regulate downstream genes responsible for antioxidant proteins, as well as phase II detoxification enzymes, and phase III transporters (Taguchi et al, 2011), alterations to the expression of Nrf2-related genes caused by MeHg exposure has not been documented.…”
Section: Introductionmentioning
confidence: 99%
“…Nuclear factor erythroid 2-related factor 2 (Nrf2), a basic leucine zipper transcription factor, has been reported as a biological defense factor against methylmercury toxicity (Toyama et al, 2007;Wang et al, 2009;Toyama et al, 2011). However, it is not clear which other transcription factors may be involved in reducing methylmercury toxicity.…”
Section: Introductionmentioning
confidence: 99%